Influence of diisocyanate structure on the morphology and properties of waterborne polyurethane-acrylates - Peruzzo, Pablo José (2012)
Polyurethane (PU)-acrylic hybrid composites were prepared by emulsion polymerization of acrylic monomers in the presence of preformed PU chains containing polymerizable terminal vinyl groups. To study the effect of the nature of diisocyanate on the film's morphology and properties, composites were prepared from two different diisocyanates: tetramethylxylene diisocyanate and 4,4′-dicyclohexylmethane diisocyanate. The samples were then characterized using size exclusion chromatography, dynamic light scattering, transmission electron microscopy, Fourier-transformed infrared spectroscopy (FTIR) and small-angle X-ray scattering (SAXS), and the gel fraction content and mechanical properties of the films were also determined. The hybrid composites were found to be cross-linked systems that underwent changes in their particle and film morphologies with increasing acrylic content. The FTIR results revealed a good interaction between the PU and acrylic moieties, and SAXS experiments showed that systems with up to a 50 wt% acrylic component were homogeneous. An attempt to incorporate a higher amount of acrylic component resulted in phase-separated materials. The composition at which phase separation was observed was found to be strongly dependent on the diisocyanate structure. Although the properties of hybrid samples with lower acrylic contents were dependent on the diisocyanate used, samples with higher acrylic contents behaved similarly to those of pure acrylic regardless of the diisocyanate used for preparation.